Capital structure and firm performance: Agency theory application to Mediterranean aquaculture firms. Issue 4 (2nd October 2021) - Ankamah-Yeboah, Isaac; Nielsen, Rasmus; Llorente, Ignacio
Abstract: The study uses firm level panel data to determine performance-leverage relationships among Mediterranean aquaculture production firms in Croatia, Italy, Spain, France and Greece. A stochastic frontier production function is used to determine and define performance through firm level efficiency estimates. The multilevel internal instrument variable approach is employed to identify the causal relationships between performance and leverage. Our results show that technical efficiency has been increasing across all firms over the period 2008–2016. The agency-cost hypothesis holds such that leverage has an inverted U-shaped relationship with performance. This implies that leverage increases with efficiency, but efficiency begins to decrease at sufficiently higher levels of leverage. The reverse relationship confirms the franchise-value hypothesis, which states that firms with high efficiency will try to protect the value of their high income by holding more equity capital. Implications for the results are drawn for the Mediterranean region.